Identification of Dimensions and Components Explaining Supportive Actions Affecting Health and Academic Success of Clients - Motaghaedi, Vahid; Jabbari, Negin; Farhadi Mahale, Ali (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The purpose of the present study was to design and validate a model of supportive actions affecting the health and academic success of clients. The research method was mixed. Methods and Materials: The statistical population in the qualitative section consisted of professors in educational sciences, educational management, and curriculum planning in higher education institutions, as well as senior managers of the education system and the State Welfare Organization. In the validation section, senior and middle managers of the Golestan Province Department of Education and the State Welfare Organization, along with experts in this field in the province, participated. In the quantitative section, senior, middle, and operational managers from the Golestan Province Department of Education and the State Welfare Organization, totaling 250 individuals, were included. In the qualitative section, 20 experts were selected using the snowball sampling method; in the validation section, 22 experts were selected by purposive sampling; and in the quantitative section, 152 individuals were chosen using stratified sampling and Cochran's formula. For data analysis, grounded theory with open, axial, and selective coding was applied in the qualitative section with semi-structured interviews as the tool. In the validation section, the Delphi method was used over three stages with a checklist for expert evaluation, and SPSS software was utilized. In the quantitative section, structural equation modeling was conducted with a 105-item questionnaire using Smart PLS software. For validity and reliability determination, in the qualitative section, necessary checks such as acceptability (expert review) and confirmability (expert verification) were used. Findings: In the validation section, the content of the expert evaluation checklist was confirmed by five academic and organizational experts for comprehensibility and clarity, and its reliability was calculated and confirmed with a test-retest method, resulting in a score of 0.84. In the quantitative section, the validity of the questionnaires was confirmed through three methods: face, content, and construct validity (convergent validity range between 0.563 and 0.676, and divergent validity greater than the correlation of the construct with other constructs). Reliability was also estimated and confirmed by three methods: calculating item factor loadings, Cronbach's alpha for components (ranging from 0.766 to 0.874), and composite reliability (ranging from 0.851 to 0.908). Conclusion: Based on the results of the qualitative and validation sections, the paradigmatic model consisted of 10 main categories (dimensions) and 20 subcategories (components), including causal conditions (responsibility towards society, religious and spiritual beliefs, social and security disorders, and cultural and physical abnormalities), contextual conditions (prevailing culture in society, people's awareness and knowledge, government support, and government-public relations), intervening conditions (mass media and social media advertising, benchmarking, the performance of non-governmental organizations, and the performance of relevant governmental organizations), strategy (social culture-building, justice orientation, economic policies, and sustainable development plans), and outcomes (scientific advancement, physical health, mental health, and public satisfaction). The quantitative results showed that all dimensions and components of the research model were confirmed.